2015
DOI: 10.1017/s0144686x15000690
|View full text |Cite
|
Sign up to set email alerts
|

How important are state transfers for reducing poverty rates in later life?

Abstract: Financial welfare in later life is of prime concern as the funding of pensions and care rises up policy agendas. In this context, work and family histories are well known to impact on late-life income, generally reducing state and private pensions for women. In a political context where benefits are under threat as part of the retrenchment of the welfare state, we consider two key questions. First, how do state pension and benefit transfers interact with work and family histories to reduce poverty risks in lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Winefield and Air (2010) suggested that grandmothers belonging to older generations were more satisfied in their grandparental role than grandfathers because they viewed it as an extension of their maternal role. Marital and work lifecourse characteristics might differ by gender and also contribute to the gender gap in the association between grandparenthood and SWB (Price et al 2015).…”
Section: Grandparenthood and Its Gendered Naturementioning
confidence: 99%
“…Winefield and Air (2010) suggested that grandmothers belonging to older generations were more satisfied in their grandparental role than grandfathers because they viewed it as an extension of their maternal role. Marital and work lifecourse characteristics might differ by gender and also contribute to the gender gap in the association between grandparenthood and SWB (Price et al 2015).…”
Section: Grandparenthood and Its Gendered Naturementioning
confidence: 99%
“…The ELSA indicated that only one-quarter of women and one-third of men aged 65 and over successfully escape from poverty without public pensions, which plays a mediating role offsetting the disadvantages of employment and family history in the lifecourse (Price et al . 2016). In developing countries, the impact of pensions on poverty reduction is almost entirely due to social pensions, also called tax-financed pensions, which are non-contributory pensions financed by the public purse.…”
Section: Pensions and Social Inclusion For Older Peoplementioning
confidence: 99%
“…Relatedly, Möhring (2015) maintains that basic and targeted pension schemes, which guarantee a basic pension to everyone who meets minimal requirements, mitigate disadvantages from discontinuous employment careers. Price et al (2016) show that non-means-tested disability benefits can be crucial in keeping otherwise poor social groups above the poverty line. Existing research has also stressed the role of private pensions for RIGs (Ginn and Arber 2001).…”
Section: Explaining Cross-national Differences In the Retirement Incomementioning
confidence: 99%